Insidensi Penyakit, Identifikasi dan Keragaman Bakteri Burkholderia glumae, Penyebab Penyakit Busuk Bulir pada Beberapa Varietas Padi di Jawa Barat - Widarti, Ani; Giyanto, Giyanto; Mutaqin, Kikin Hamzah (Jurnal Fitopatologi Indonesia, 2020)
Incidence of Bacterial Grain Rot Disease, Identification, and Diversity of Burkolderia glumae in Some Rice Varieties in West JavaRice rot disease caused by the bacteria Burkholderia glumae needs to be looked out, including in West Java as one of rice production center for Indonesia. This study was carried out to determine disease incidence, identity and diversity of B. glumae in several rice varieties grown in West Java Province. Sampling and observation of disease incidence were conducted in 9 districts.  Bacteria were isolated from rice grains with symptomatic rot, followed by biochemical and physiological tests involving Gram and growing tests at pH 4.8 and 2% NaCl.  Phenotypic variation was observed from the colony color on S-PG media, toxofalvin production, hypersensitivity response to tobacco leaves, and pathogenicity test on rice plants.  B. glumae specific primers, JLBgF/JLBgR, and bacteria universal 16S rRNA primers, 27F/1492R were used to determine molecular identity. Genotypic diversity analysis was performed using neighbour-joining tree method. Disease incidence was in the range of 0–73.3%, the highest was found in Dawuan District (Karawang) on var. Mekongga. The phenotypic observations showed 10 isolates belonging to type A colonies and 19 isolates of type B; 25 isolates produced toxoflavin; 29 isolates produced hypersensitivity responses to tobacco leaves and blight symptoms in rice plants. Identification using specific and universal primers confirmed that 29 isolates were B. glumae. The genotypic diversity analysis of 16S rRNA gene showed that KRCH-2 isolates (Karawang) and INCH-6 (Indramayu) were closely related to B. glumae from China and America.